Developing new sustainable strategy: The struggle of small and medium Swedish contractors companies to experiment with business models - Martine Buser; Veronica Carlsson (Journal of Business Models (JOBM), 2020)
Purpose: This paper analyses the efforts and challenges met by Small and Medium contractors to develop new business models when struggling to implement retrofit solutions for s ingle house owners' renovation. Design/methodology/approach: The paper builds on a four years action research project with 21 Swedish contractors from the Gothenburg region testing the business model canvas to develop energy efficient solutions. The project method includes 67 interviews with craftsmen and their customers, 18 workshops gathering the companies in two groups to develop new sustainable business models and 16 shadowing of visit s to their customers. Findings: Our study underlines how SMEs contractors concentrated on their technical core business tend to underestimate their customer relationship. Both customer segments and relationships escape from formalisation as these companies do not dare to exclude any client and are inclined to reduce customer relationship to personal interaction. Besides, these project base companies are challenged by the blocks presented by the canvas and struggle to match the model with their own organisation. Original value: Differently to most research on business models and sustainability this paper addresses the concrete difficulties construction SMEs face when implementing business models.
Keywords: 650; Business models; constructions SMEs; sustainability